Conexão de orações: expressão do tempo em redações de alunos do segundo segmento do ensino fundamental - Lima, Maria Luiza Macêdo de (2012)
In this article are analyzed, with the parameters proposed by Lima- Hernandez (2004), forms of sentences connection involving expression of time. It is intended here, with the backing of theoretical linguistic functionalism, verify and quantify, in percentage terms, the ways in which the notion of time is established in student’s writings, seeking to uncover the motivations that influence this organization. In the results, we highlight evidence that the manifestation of time in complex sentences takes place preferentially through hypotactic finite clauses, with a clear preference in terms of ordering by allocating in initial position the sentence that carries the time expression.